LIFE SKILL DALAM PEMBELAJARAN KEWIRAUSAHAAN DI SMK 1 SWADHIPA NATAR LAMPUNG SELATAN - Supriyanto Supriyanto; Pargito Pargito; R. Gunawan Sudarmanto (Faculty of Teacher Training and Education, University of Lampung, 2013)
The objectives of this research were to construct and implement life skill in entrepreneurship learning in Swadhipa 1 Senior Vocational School in Natar of South Lampung. This was a qualitative research with constructionist approach. The results were that (1) life skill construction in entrepreneurship learning was an integration process of life skill through entrepreneurship learning with a purpose to give learners life ability skills. The life skill constructionistic in entrepreneurship learning was that there were differences of concept understandings with the real applications or the differences between life skill integration process and learning result; (2) the life skill implementation in entrepreneurship learning included: (a) entrepreneurship lesson plans made by teachers did not yet include explicit life skill into learning aids. However, implicitly all teachers had applied it properly into learning indicators, even though developed activities were still partial and not continuous; (b) learning conduct were still dominated by teachers using lecturing method. Trends in learning processes were stockpiling concepts, not to develop learners’ life skill; and (c) assessments conducted by teacher were merely in cognitive domains, and there were no evaluation instrument developments based on life skill.Keywords: life skill, entrepreneurship, constructionistic